2021
DOI: 10.3390/molecules26237383
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Variation of Metabolites, Mineral Elements and Antioxidant Activities of Rhodiola crenulata (Hook.f. & Thomson) H.Ohba

Abstract: Rhodiolacrenulata (Hook.f. & Thomson) H.Ohba is an alpine medicinal plant that can survive in extreme high altitude environments. However, its changes to extreme high altitude are not yet clear. In this study, the response of Rhodiola crenulata to differences in altitude gradients was investigated through chemical, ICP-MS and metabolomic methods. A targeted study of Rhodiola crenulata growing at three vertical altitudes revealed that the contents of seven elements Ca, Sr, B, Mn, Ni, Cu, and Cd, the phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 123 publications
(161 reference statements)
2
0
0
Order By: Relevance
“…In our case, total polyphenols and flavonoid concentrations slightly increased with altitude, consistent with observations made by other researchers [ 47 , 50 ]. The samples from the 792 m site differed from the trend, potentially due to variations in pedological composition, elevated humidity during the collection period, or other ecological factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our case, total polyphenols and flavonoid concentrations slightly increased with altitude, consistent with observations made by other researchers [ 47 , 50 ]. The samples from the 792 m site differed from the trend, potentially due to variations in pedological composition, elevated humidity during the collection period, or other ecological factors.…”
Section: Discussionsupporting
confidence: 93%
“…Another study pointed out low concentrations of tannins at high altitudes [ 53 , 54 ]. The accumulation of condensed tannins with altitude was reported in other studies [ 50 , 55 ]. Analyzing separately low-molecular-weight polyphenols (LMP) and high-molecular-weight polyphenols—tannins (HMP), other authors [ 56 ] showed that the concentration of HMP was positively correlated with altitude, unlike LMP accumulation, which was independent of altitude in the species as Pteridium caudatum (L.) Maxon and Pteridium arachnoideum (Kaulf.)…”
Section: Discussionsupporting
confidence: 74%